Social eXtended Reality (XR) and Virtual Production: Crafting New Frontiers in Immersive Storytelling - Benavente, Álvaro Egea; Cabré, Marc Martos; Montesa, Javier; Ibañez, Francisco; Fernández, Sergi; Climent, Mario Montagud (Proceedings of the ACM International Conference on Interactive Media Experiences Workshops (IMXw); 2025: Proceedings of the ACM International Conference on Interactive Media Experiences WorkshopsDO - 10.5753/imxw.2025.1505, 2025)
Immersive technologies are transforming how we consume, interact and engage with media. In this context, Social eXtended Reality (XR) is emerging as a powerful medium for remote communication, social interaction, and shared virtual experiences. Simultaneously, advances in multi-modal virtual production tools are expanding the boundaries of immersion, interactivity, and narrative design —while enabling the scalable distribution of rich immersive experiences via traditional 2D video platforms. This paper explores new frontiers in interactive and immersive storytelling through the convergence of Social XR, holographic communication, and virtual production. First, it proposes a cohesive architectural framework to seamlessly integrate innovative tools from these technological domains, aiming to support diverse interaction and media presentation modalities. Second, it outlines potential use cases and presents preliminary findings that demonstrate the feasibility and transformative potential of such newly envisioned cross-technology integration.